Social-cultural Functions of Rice Farming Systems - Prihtanti, Tinjung Mary; Hardyastuti, Suhatmini; Hartono , Slamet; Irham (Asian Journal of Agriculture and Rural Development, 2014)
This study examines social-cultural function that arise on wet-land rice cultivation system. The observations and data analysis showed that employment absorption and emergence of social cohesion among farmers that enhance the technological innovation of organic rice cultivation were felt due to the application of organic farming system. Organic rice farming systems tend to gave higher economic value as labor absorber, but this study found that organic rice farming system did not guarantee farming tradition maintenance and increasing of farmer women participation.